The miRNA biogenesis in marine bivalves - Rosani, Umberto; PALLAVICINI, Alberto; Venier, Paola (PeerJ, 2016)
Small non-coding RNAs include powerful regulators of gene expression, transposon mobility and virus activity. Among the various categories, mature microRNAs (miRNAs) guide the translational repression and decay of several targeted mRNAs. The biogenesis of miRNAs depends on few gene products, essentially conserved from basal to higher metazoans, whose protein domains allow specific interactions with dsRNA. Here, we report the identification of key genes responsible of the miRNA biogenesis in 32 bivalves, with particular attention to the aquaculture species Mytilus galloprovincialis and Crassostrea gigas. In detail, we have identified and phylogenetically compared eight evolutionary conserved proteins: DROSHA, DGCR8, EXP5, RAN, DICER TARBP2, AGO and PIWI. In mussels, we recognized several other proteins participating in the miRNA biogenesis or in the subsequent RNA silencing. According to digital expression analysis, these genes display low and not inducible expression levels in adult mussels and oysters whereas they are considerably expressed during development. As miRNAs play an important role also in the antiviral responses, knowledge on their production and regulative effects can shed light on essential molecular processes and provide new hints for disease prevention in bivalves.